IMPROVING FINANCIAL PERFORMANCE THROUGH ISLAMIC CORPORATE GOVERNANCE, ISLAMIC CORPORATE SOCIAL, AND INTELLECTUAL CAPITAL - YUSVITA NENA; ISTIANA LAILAULFA (Institut Bisnis Muhammadiyah Bekasi, 2021)
The rapid development of Islamic banks requires Islamic banks to continue to create value as a competitive advantage and demonstrate the healthy performance of Islamic banks. There are several determinant factors as the creator of added value, namely Islamic Corporate Governance, Islamic Corporate Social, and Intellectual Capital. With the increase in the added value factor, the performance of Islamic banks will improve and be able to absorb the market share of Islamic banks to be wider. Islamic Bank Financial Performance in this study uses the measurement of the Islamix Performance Index (IPI). By using the analysis tool EViews 9, the results of a partial regression test are obtained that the three factors that add value to the company, namely ICG, ICSR, IC, affect the financial performance of Islamic banks.